2015
DOI: 10.1039/c5ta04936a
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale aligned crystalline CH3NH3PbI3 perovskite array films

Abstract: Owing to the lattice match, large-scale aligned crystalline CH3NH3PbI3 perovskite array films were fabricated on ST cut quartz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Additionally, only a few of them have demonstrated broad wavelength tunability. These shortages are possibly solved by the recently discovered perovskites, which are directly synthesized from solution at room temperature . The emission and absorption wavelengths of hybrid lead halide CH 3 NH 3 PbX 3 (MAPbX 3 , X = Cl, Br, I) can be widely tuned from blue light to near infrared by changing their stoichiometric composition in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, only a few of them have demonstrated broad wavelength tunability. These shortages are possibly solved by the recently discovered perovskites, which are directly synthesized from solution at room temperature . The emission and absorption wavelengths of hybrid lead halide CH 3 NH 3 PbX 3 (MAPbX 3 , X = Cl, Br, I) can be widely tuned from blue light to near infrared by changing their stoichiometric composition in solution.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we reported the crystal structure match of the (010) plane of CH 3 NH 3 PbI 3 to the surface lattice of ST-cut quartz [35]. Both the lattice spacings of (001) and (101) planes of CH 3 NH 3 PbI 3 and the crystal face angle fit the structural periodicity of ST-cut quartz.…”
Section: Introductionmentioning
confidence: 73%
“…Even without a precisely prepared substrate, an aligned NWA can still be formed. [74][75][76] For instance, Deng et al fabricated a highly crystalline compact microwire array by blade coating MAPbI 3 solution (Figure 3f ). [74] In this process, the speed of the blade and precursor concentration is found to have critical effects on the final NW, and with suitable parameters, the obtained NW was verified as single crystalline (Figure 3g).…”
Section: Oriented-force-induced Growthmentioning
confidence: 99%
“…[42] However, the use of these templates not only leads to increased cost but also makes it difficult to scale up. Therefore, many other preparation methods, including blade coating, [115] slip coating, [75] and roll-to-roll microgravure printing, [79] have been studied to address this dilemma. These perovskite microwires can reach up to a centimeter in length, and the corresponding device can realize a specific detectivity of 10 12 Jones.…”
Section: Single-functional Nmws-based Photodetectorsmentioning
confidence: 99%